Study of autosomal STR loci with IBS method in full sibling identification. (May 2017) - Yuan, Li; Xu, Xu; Zhao, Dong; Ren, He; Hu, Chaohui; Chen, Wen; Hao, Shicheng; Lu, Di; Zhang, Lin
Graphical abstract: Highlights: A total of 342 pairs of full sibs (FSs) and 3900 pairs of unrelated individuals (UIs) were genotyped for 51 STR loci. IBS scores were analyzed and compared between groups. The discriminant functions of FS-UI were determined by using the Fisher discriminant with SPSS software. STRs with higher DP values should be selected when additional autosomal markers are required for FS identification. Discriminant analysis with the IBS method is highly applicable for the FS-UI test. Abstract: Objective: We investigated the application of 51 autosomal short tandem repeat (STR) loci with the identity by state (IBS) method and a discriminant function algorithm in full-sib identification. Methods: A total of 342 pairs of full sibs (FSs) and 3900 pairs of unrelated individuals (UIs) were genotyped for 51 STR loci. Groups were formed in accordance with discrimination power (DP) values and the number of loci, and IBS scores of FSs and UIs were analyzed and compared. The discriminant functions of FS-UI were determined by using the Fisher discriminant with SPSS software. Results: All IBS in FSs and UIs groups showed normal distributions and there were significant differences between FS-UI. Receiver operating characteristic curves revealed that the detection efficiency of full-sib identification was affected by both the locus polymorphism and the number of loci detected. Comparing the rate of false positive and false negative of discriminant function between groups, a higher average DP value and larger number of loci detected were associated with a lower rate of miscarriage of justice and were more helpful for full-sib identification. Conclusion: STRs with higher DP values should be selected when additional autosomal markers are required for FS identification. Discriminant analysis with the IBS method is highly applicable for the FS-UI test.